2012
DOI: 10.1007/s10554-012-0104-7
|View full text |Cite
|
Sign up to set email alerts
|

Capability of three-dimensional speckle tracking radial strain for identification of patients with cardiac sarcoidosis

Abstract: Since cardiac sarcoidosis (CS) leads to substantial morbidity and sudden death, early diagnosis and appropriate management are crucial for patients with CS. Echocardiography used to be considered a useful diagnostic tool for patients with CS, but CS may clinically present as dilated cardiomyopathy (DCM). Our objective was to investigate whether a novel three-dimensional (3-D) speckle-tracking strain can identify patients with CS more accurately. We studied 23 CS patients with an ejection fraction (EF) of 46 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Our study expands on recent publications that have suggested that indices of myocardial deformation, such as GLS, are abnormal in the presence of CS, even when other TTE parameters are within normal limits. Similarly, others have reported reduced radial 3D strain in CS patients when compared to individuals with dilated cardiomyopathy with matched LV EF …”
Section: Discussionmentioning
confidence: 99%
“…Our study expands on recent publications that have suggested that indices of myocardial deformation, such as GLS, are abnormal in the presence of CS, even when other TTE parameters are within normal limits. Similarly, others have reported reduced radial 3D strain in CS patients when compared to individuals with dilated cardiomyopathy with matched LV EF …”
Section: Discussionmentioning
confidence: 99%
“…Strain imaging has shown promising results in detecting impaired LA function and predicting recurrence of AF after anti-arrhythmic treatment. 21,[34][35][36][37] We hypothesized that in addition to volumetric LA differences, 3DSTE is also capable of detecting LA deformation changes in patients suffering from AF compared to normal healthy controls. 32,33 The more recently developed 3DSTE tries to combine the two methods by not only being able to measure volumetric changes over time in different heart chambers, but also by providing strain data based on a 3D speckle tracking algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Although requiring further validation, 1 group suggested that there may be a role for 3-dimensional (3D) speckle tracking radial strain in distinguishing CS from dilated cardiomyopathy 27 although in a different study impaired radial strain by 2D speckle tracking was not useful in identifying LGE detected by CMR, whereas circumferential and longitudinal strain exhibited a significant association. 28 Ultimately, strain imaging by echocardiography may provide a useful method to assess response to therapy 29 although to date there are no studies supporting this application.…”
Section: Use Of Strain Imagingmentioning
confidence: 99%